Impact of Cryopreservation on Spermatozoa Freeze-Thawed Traits and Relevance OMICS to Assess Sperm Cryo-Tolerance in Farm Animals - Khan, Ibrar Muhammad; Cao, Zubing; Liu, Hongyu; Khan, Adnan; Rahman, Sajid Ur; Khan, Muhammad Zahoor; Sathanawongs, Anucha; Zhang, Yunhai (Frontiers in Veterinary Science, 2021)
Sperm cryopreservation is a powerful tool for the livestock breeding program. There have been several technical attempts to improve the efficiency of sperm cryopreservation in various species of farm animals. However, it is well recognized that mammalian sperm are susceptible to cryoinjury caused by cryopreservation processes. Moreover, the factors leading to cryoinjury are complicated, and the cryo-damage mechanism is difficult to explain until now, which directly influence the quality of frozen-thawed sperm. Currently, the conducting of various OMICS technologies in sperm cryo-biology, particularly proteomics studies, has contributed while exploring the molecular alterations caused by cryopreservation, identification of various freeze-ability markers and specific proteins that could be added to semen diluents before cryopreservation to improve sperm cryo-survival. Therefore, to understand the cryoinjury mechanism of sperm is essential for the optimization of current cryopreservation processes. Recently, application of newly-emerged proteomics and transcriptomics technologies to study the effects of cryopreservation on sperm is becoming a hotspot. This review detailed an updated overview of OMICS elements involved in sperm cryo-tolerance and freeze-thawed quality. While also detailed a mechanism of sperm cryo-injury and utilizing OMICS technology that assesses the sperm freeze-ability potential biomarkers for a further accurate classification into excellent or bad freezers breeding candidates.